The roles, signalling pathways and therapeutic implications of Apoc1 in cancer - Hao-Han Guo; Qiang Guo; Qun-Xian Zhang; Dan Li; Yan Lv (Discover Oncology)
Abstract The apolipoprotein C (Apoc) family comprises a group of low-molecular-weight proteins that are essential for modulating lipoprotein metabolism, primarily influencing lipid transport and metabolic pathways. Apoc1, a member of the Apoc family, is consistently overexpressed across various cancers, significantly correlating with poor prognosis. The multifaceted role of Apoc1 includes promoting cancer progression by activating key signalling pathways such as epithelial-mesenchymal transition (EMT), mitogen-activated protein kinases (MAPK), STAT3 and WNT3 A. Additionally, Apoc1 contributes to the regulatory networks involving lncRNAs and miRNAs, thereby influencing cancer. This comprehensive review delineates Apoc1’s mechanisms within malignant tumours and assesses its prognostic implications for patients with cancer. The aim is to shed light on potential novel therapeutic strategies in oncology, potentially revolutionising patient care and thereby enhancing patient survival rates and quality of life.